Analisis Kepuasan Wisatawan Kota Surabaya dengan Model End User Computing Satisfaction (Studi Kasus: Tiket Wisata Surabaya) - Firdaus Akmal Fauzan; Asif Faroqi; Siti Mukaromah (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2025)
This research analyzes user satisfaction of the Surabaya Tourist Ticket, which is a digital platform designed to make it easier to purchase tourist tickets in the city of Surabaya which is managed by the Surabaya City DISBUDPORAPAR. This analysis was carried out using the End User Computing Satisfaction model which measures the content, accuracy, format, ease of use, and timeliness of the application. The result of the analysis shows that this application has a positive and significant influence on a user satisfaction in the content, accuracy, ease of use, and timeliness variables, but the format variable has a positive but not significant influence on the user satisfaction. From the result of this analysis, it can be seen that the Surabaya Tourist Ticket has been successful in meeting needs so that users feel satisfied. The implication of this research is to support further development to improve the appearance and maintain performance so that the existence of the Surabaya Tourist Ticket website and tourism in the city of Surabaya increase so that regional income also increases.